Potencial biorremediador de bactérias isoladas de sedimentos do estuário da Baixada Santista - Ferrari, Vitor Baptista [UNIFESP] (2017)
Brazil is considered one of leader countries in the use of sustainable techniques. Among its national territory, it is necessary some special attention to the Brazilian Coastal Zone, mainly because of the intense traffic of ships along it, which can cause oil spills, as well other related environmental accidents. Microorganisms are known about their metabolic characteristics like fast growth, quick acclimation in different environments and high genetic variability. In this context, the present study aimed to investigate the aerobic bacterial diversity of sediments of the Santos estuary (SP, Brazil) regarding to the metabolic activities allowing hydrocarbon biotransformation. From a total of 42 bacterial isolates, twenty-one (21) were selected as potential biodegraders of hexadecane, using a solution of 3- (4,5-dimethyl-2-thiazolyl) -2,5-diphenyl- 2 H-tetrazolium bromide 1% (MTT, Merck) as indicator of microbial viability. Analyzes of Gas Chromatography Coupled to Mass Spectrometry (GC-MS) were performed to verify the biodegradation indexes of hexadecane by the selected isolates. Six (6) isolates were detected as able to biodegrade hexadecane, showing indexes above 97%. They were able to degrade 80 % of the hydrocarbon after 48 h of incubation. In addition, Emulsification Indexes (E24) assays allowed the selection of three bacterial strains producing metabolites with bioemulsifying potential, showing E24 values around 50 %. The isolates were characterized by molecular analyzes based on 16S rDNA. They were affiliated to the genus Bacillus sp., Staphylococcus sp., Micrococcus sp., Nitratireductor sp. and Klebsiella sp.